Researchers Simplify Parallel Programming. - Anthes, Gary (Communications of the ACM, 2014)
The article discusses the Massachusetts Institute of Technology (MIT), Microsoft Research and the Israel Institute of Technology's study which showed that lock-free algorithms performed as effectively as wait-free algorithms. Topics discussed include the importance of parallel computing in chip manufacturing and the two types of algorithms as part of class of techniques used in shared-memory systems, the evolution of parallel computation, the use of lock-free algorithms by programmers and the transactional memory as a lock-free control method.